2013
DOI: 10.1152/japplphysiol.01099.2012
|View full text |Cite
|
Sign up to set email alerts
|

Progressive improvement in hemodynamic response to muscle metaboreflex in heart transplant recipients

Abstract: Exercise capacity remains lower in heart transplant recipients (HTRs) following transplant compared with normal subjects, despite improved cardiac function. Moreover, metaboreceptor activity in the muscle has been reported to increase. The aim of the present investigation was to assess exercise capacity together with metaboreflex activity in HTR patients for 1 yr following heart transplant, to test the hypothesis that recovery in exercise capacity was paralleled by improvements in response to metaboreflex. A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 38 publications
4
48
0
Order By: Relevance
“…Moreover, our group has recently demonstrated that MS patients had an altered hemodynamic response to metaboreflex activation (Marongiu et al, 2015). This response resembled that showed by patients with cardiovascular and metabolic disease, where the target blood pressure is reached mainly by means of vasoconstriction (Piepoli et al, 2008; Delaney et al, 2010; Dipla et al, 2010; Choi et al, 2013; Crisafulli et al, 2013; Milia et al, 2015b). In healthy subjects, during the metaboreflex, a cardiac output-mediated mechanism is primarily responsible for the normal increase in mean blood pressure (MBP; Crisafulli et al, 2003, 2008; Delaney et al, 2010; Roberto et al, 2012; Spranger et al, 2013).…”
Section: Introductionsupporting
confidence: 73%
See 3 more Smart Citations
“…Moreover, our group has recently demonstrated that MS patients had an altered hemodynamic response to metaboreflex activation (Marongiu et al, 2015). This response resembled that showed by patients with cardiovascular and metabolic disease, where the target blood pressure is reached mainly by means of vasoconstriction (Piepoli et al, 2008; Delaney et al, 2010; Dipla et al, 2010; Choi et al, 2013; Crisafulli et al, 2013; Milia et al, 2015b). In healthy subjects, during the metaboreflex, a cardiac output-mediated mechanism is primarily responsible for the normal increase in mean blood pressure (MBP; Crisafulli et al, 2003, 2008; Delaney et al, 2010; Roberto et al, 2012; Spranger et al, 2013).…”
Section: Introductionsupporting
confidence: 73%
“…During both the PEMI and the CER test, hemodynamics was assessed by means of impedance cardiography (NCCOM 3, BoMed Inc., Irvine, CA), which has already been used in similar experimental settings (Crisafulli et al, 2007, 2008, 2013; Roberto et al, 2012). The data acquisition method is described in detail in our previous published papers (Crisafulli et al, 2007, 2008, 2013; Roberto et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three minutes of recovery were further allowed after the cuff was deflated, for a total of 6 min of recovery. This protocol has been shown to trap the muscle metabolites in the exercising limb and to maintain stimulation of the metaboreceptors (9,15,29,49).…”
Section: Study Populationmentioning
confidence: 99%